Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/jnr.20880
|View full text |Cite
|
Sign up to set email alerts
|

Maturation-dependent oligodendrocyte apoptosis caused by hyperoxia

Abstract: In the immature human brain, periventricular leukomalacia (PVL) is the predominant white matter injury underlying the development of cerebral palsy. PVL has its peak incidence during a well-defined period in human brain development (23-32 weeks postconceptional age) characterized by extensive oligodendrocyte migration and maturation. We hypothesized that the dramatic rise of oxygen tissue tension associated with mammalian birth and additional oxygen exposure of the preterm infant during intensive care may be h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
64
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 56 publications
8
64
0
Order By: Relevance
“…Recently, we found that hyperoxia triggers maturationdependent apoptosis in immature (O4ϩO1ϩMBPϪ) and preOLs (O4ϩO1ϪMBPϪ), which is dependent on caspase activation (Gerstner et al, 2006). This study used the oligodendroglial cell line OLN-93 (Richter-Landsberg and Heinrich, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we found that hyperoxia triggers maturationdependent apoptosis in immature (O4ϩO1ϩMBPϪ) and preOLs (O4ϩO1ϪMBPϪ), which is dependent on caspase activation (Gerstner et al, 2006). This study used the oligodendroglial cell line OLN-93 (Richter-Landsberg and Heinrich, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperoxia has been implicated in the pathogenesis of bronchopulmonary dysplasia and retinopathy of prematurity (Saugstad, 2001;Chow et al, 2003). There is increasing evidence that hyperoxia may negatively influence brain maturation and development (Collins et al, 2001;Felderhoff-Mueser et al, 2004;Klinger et al, 2005;Gerstner et al, 2006). However, the mechanism of hyperoxia-induced injury and the identification of vulnerable cells in the human brain are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In light of decreased penumbral caspase-8 cleavage with NBO (Liu et al, 2006), it can be speculated that treatment with NBO only delays initiation of early stages of apoptosis but ultimately cannot prevent cell death (Wang and Lenardo, 2000). Potentially, reactive oxygen speciesmediated mitochondrial damage could lead to caspase-9 activation, leading to cell death through effector caspases such as caspase-6 (Gerstner et al, 2006;Lee and Choi, 2003;Wang and Lenardo, 2000); however, further studies are necessary to confirm these hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle analysis including detection of apoptotic cells was performed as described previously (15). Data analysis was performed in WIN MDI 2.8 and the Cylchred program (see www.facslab.toxikologie.uni-mainz.de).…”
mentioning
confidence: 99%